Human Resource Development for Enhancing Employee Performance: A Case Study of the Ministry of Religious Affairs Office in Yogyakarta - Ahmad Zuhdan Makhluf; Rahmat Riadi; Aunur Rahmah Faqiyah Muchtar (Islamic Education Management Study Program, Faculty of Tarbiyah and Education State Islamic University (UIN) Sunan Kalijaga Yogyakarta, Indonesia, 2024)
Purpose – This study investigates the human resource development (HRD) management practices at the Ministry of Religious Affairs Office in Yogyakarta, which is recognized for its high-quality human resources and numerous achievements. Design/methods – The study employs a qualitative methodology, utilizing observations, interviews, and documentation to collect data. The focus is on the Ministry's innovative HRD programs and their impact on employee performance. Findings – Key findings indicate that the Ministry's initiatives, including the One-Stop Service and Collaborative Service System with Jogja Smart Service, have significantly improved public satisfaction and employee effectiveness. These HRD strategies showcase effective planning and continuous evaluation. Research implications/limitations – The study acknowledges limitations such as its focus on a single office and reliance on qualitative data, which may introduce subjectivity. Future research should include a broader scope and employ quantitative methods to validate and expand upon these findings, enhancing the generalizability of HRD principles. Practical implications – The study provides valuable insights for HRD practitioners and policymakers, emphasizing the importance of structured HRD programs and strategic planning in improving organizational performance and employee outcomes. Originality/value – This research contributes to the broader HRD literature by offering empirical evidence from a governmental context, underscoring the applicability of HRD principles across different sectors and demonstrating the success of innovative HRD practices in a public institution.